Acute and Persistent Cardiovascular Effects of Menthol E‐Cigarettes in Mice - Ramalingam, Anand R.; Kucera, Cory; Srivastava, Shweta; Paily, Romith; Stephens, Dawson; Lorkiewicz, Pawel; Wilkey, Daniel W.; Merchant, Michael; Bhatnagar, Aruni; Carll, Alex P. (Journal of the American Heart Association, 2025)
Although e-cigarettes provide an alternative to conventional smoking, the cardiovascular impacts of e-cigarette use are unresolved. The popularity of menthol e-cigarettes has surged recently and may escalate further with bans on combustible menthol cigarettes and e-cigarette flavors other than menthol and tobacco. Despite recent evidence in mice that menthol e-cigarettes acutely induce cardiac arrhythmias, the impacts of repeated menthol e-cigarette use on cardiovascular function and the cardiac proteome remain unclear. We therefore investigated the acute and persistent cardiovascular effects of menthol e-cigarettes in a mouse model. Adult C57BL/6J mice with ECG and blood pressure radiotransmitters were exposed to e-cigarette aerosols (180-270 puffs/day; n=4-8/group). One-day exposures to nicotine-containing e-cigarette aerosols depressed heart rate variability regardless of flavor, but menthol e-cigarette aerosols uniquely increased heart rate and urine epinephrine and elicited spontaneous ventricular premature beats. Menthol e-cigarette aerosols consistently increased blood pressure acutely, and this effect recurred throughout the 20-day regimen. Pretreatment with atenolol abolished e-cigarette-induced arrhythmias, suggesting the involvement of β1-adrenoceptors. After 4 weeks of exposure to JUUL Menthol aerosol, mice had basal sinus bradycardia that persisted up to 3 weeks after exposure cessation. After cessation, e-cigarette-exposed mice also exhibited an altered chronotropic response to restraint stress and prolonged ventricular repolarization (corrected QT interval). Integrated proteomic and phosphoproteomic analysis of cardiac tissue harvested from mice exposed to menthol e-cigarette aerosols for 5 and 20 days revealed molecular signatures of dilated and arrhythmogenic cardiomyopathy. Exposure to menthol e-cigarette aerosols induces persistent cardiovascular autonomic imbalance in vivo. These findings raise the possibility of similar effects in humans using mentholated e-cigarettes.